Understanding property law - Sprankling, John G. (Understanding series (New York, N.Y.), 2023)
"'Understanding Property Law' is a comprehensive and authoritative treatise designed for law students who are taking the standard first-year course on property. It (1) explains the basic principles of property law in the United States and (2) discusses the policy concerns and historical currents that shape this law. The goal of the book is simple: to help students understand property law. It is suitable for use with any casebook. This book provides complete coverage of all standard topics covered in the basic property course, including landlord-tenant law, adverse possession, rights in personal property, intellectual property, estates and future interests, cotenancies, marital property, sales transactions, mortgages, easements, covenants, servitudes, nuisances, eminent domain, zoning, takings, and other land use issues. In addition, the book analyzes cutting-edge issues in modern property law, such as rights in human body parts, current takings issues, judicial reactions to the Restatement (Third) of Property: servitudes, rights and duties of homeowners associations, and rights in personal names and likenesses. Its clear writing and detailed organization help students understand both basic concepts and controversial issues. Thousands of law students across the nation have succeeded in their property classes by using this book."-- Provided by publisher